2020
DOI: 10.1038/s41598-020-58510-9
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptome-wide association study based on 27 tissues identifies 106 genes potentially relevant for disease pathology in age-related macular degeneration

Abstract: Genome-wide association studies (GWAS) for late stage age-related macular degeneration (AMD) have identified 52 independent genetic variants with genome-wide significance at 34 genomic loci. Typically, such an approach rarely results in the identification of functional variants implicating a defined gene in the disease process. We now performed a transcriptome-wide association study (TWAS) allowing the prediction of effects of AMD-associated genetic variants on gene expression. The TWAS was based on the genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 73 publications
1
39
0
Order By: Relevance
“…Remarkably, with exception of the study by Orozco et al (2020) [ 28 ], an AMD-associated regulation of the genes PILRA and PILRB was reported in all studies and consistently showed an upregulation with increased AMD risk. Another three loci (see “ CFI ”, “ C2/CFB/SKIV2L ”, and “ RDH5/CD63 ”) revealed gene regulatory effects predominantly in retina in comparison to data available from extraocular tissues [ 31 , 33 ] (category 2). The gene HLA-DQB1 (locus “ C2/CFB/SKIV2L ”) is part of the major histocompatibility complex and was explicitly excluded in the TWAS by Strunz et al (2020).…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Remarkably, with exception of the study by Orozco et al (2020) [ 28 ], an AMD-associated regulation of the genes PILRA and PILRB was reported in all studies and consistently showed an upregulation with increased AMD risk. Another three loci (see “ CFI ”, “ C2/CFB/SKIV2L ”, and “ RDH5/CD63 ”) revealed gene regulatory effects predominantly in retina in comparison to data available from extraocular tissues [ 31 , 33 ] (category 2). The gene HLA-DQB1 (locus “ C2/CFB/SKIV2L ”) is part of the major histocompatibility complex and was explicitly excluded in the TWAS by Strunz et al (2020).…”
Section: Resultsmentioning
confidence: 92%
“…Strunz et al (2020) performed an eQTL mega-analysis using three datasets based on 311 retinal tissue samples of exclusively healthy donor eyes, including 94 control samples of Ratnapriya et al (2019) [ 25 , 32 ]. Two further studies targeted gene expression regulation in extraocular tissues including 588 liver tissue samples from four independent studies [ 31 ], and various tissues originating from the GTEx database as well as individual genotype data from the IAMDGC sample set [ 8 , 33 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations